Continuum limits of pattern formation in hexagonal-cell monolayers - O'Dea, Reuben D.; King, John R. (Springer, 2012)
Intercellular signalling is key in determining cell fate. In closely packed tissues such as epithelia, juxtacrine signalling is thought to be a mechanism for the generation of fine-grained spatial patterns in cell differentiation commonly observed in early development.